2013
DOI: 10.17221/82/2012-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of common beech (Fagus sylvatica L.) along the altitudinal gradient in Slovakia (Inner Western Carpathians)

Abstract: ABSTRACT:The onset and course of selected vegetative phenological phases of beech along the altitudinal gradient in Slovak Republic were studied. Observations were done in the Burda Mts. (200-300 m a.s.l.), Kremnické vrchy Mts. (500 m a.s.l.) and in the Poľana Mts. (900-1,000 m a.s.l., 1,200-1,400 m a.s.l.). Selected spring phenological phases (budburst and leaf unfolding) as well as autumn phenological phases (autumn colouring and leaf fall) were investigated over the period of 5 years (2007)(2008)(2009)(2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
5
12
0
1
Order By: Relevance
“…The phenological elevation gradient of nut ripeness reached 2.9 days per 100 elevation meters, which confirms that differences between the sites are considerably smaller than in the case of the spring phenological phase. Similar results were also presented by Schieber et al (2013), who showed that the site differences in average onsets of autumn vegetative phenophases of common beech were significantly lower (1-1.78 day/100 m) than those of spring phenophases.…”
Section: Resultssupporting
confidence: 87%
“…The phenological elevation gradient of nut ripeness reached 2.9 days per 100 elevation meters, which confirms that differences between the sites are considerably smaller than in the case of the spring phenological phase. Similar results were also presented by Schieber et al (2013), who showed that the site differences in average onsets of autumn vegetative phenophases of common beech were significantly lower (1-1.78 day/100 m) than those of spring phenophases.…”
Section: Resultssupporting
confidence: 87%
“…During the period of leaf development the average temperature at high altitude was lower in comparison to the low altitude site. Moreover, even within the small altitudinal range of 311 m in our study site, leaf unfolding in beech was affected by 1.6e4.8 days per 100 m of an increase in altitude (see also Cufar et al, 2012;Schieber et al, 2013;Vitasse et al, 2009).…”
Section: Ambient Temperature and Leaf Phenologymentioning
confidence: 83%
“…Long-time studies investigating the timing of plants' leaf phenology (Schaber and Badeck, 2005) and insects' (Van Asch et al, 2013) or birds' reproduction (Both et al, 2004) found markedly shifts into earlier season; but not all species seem to shift their phenology to the same extent (see review of Visser and Both, 2005). Shifts in timing also appear according to temperature changes along altitudinal gradients in plants' leaf phenology (Schieber et al, 2013), insects' activity patterns (Ill an et al, 2012) and birds' breeding behavior (Martin et al, 2009). Thus, these shifts lead to later seasons in colder, higher altitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a common trait that altitude has an impact on the duration of the vegetation period as can be corroborated in the regional phenology studies of the common beech [42,43]. The earliest onset of the spring phenological phases is observed in the lowest-lying sites and the latest onset in the uppermost sites.…”
Section: Photosynthetic Activity (Fapar) Of Beech Ecosystemsmentioning
confidence: 74%